Regional variation of risk factors among diabetic retinopathy patients in India: Findings from the INDO EYE study - Gopal S Pillai; Bibhuti Prassan Sinha; C. S. Sheeba; Manabjyoti Barman; Alok Sen; Natarajan Sundaram; Merin Dickson; Ashid Salim; Geethu Paul; Deepthi Geetha KrishnanNair; Manjisa Choudhury; Aniket Kumar; et al. (Journal of Clinical Ophthalmology and Research)
Context: Diabetic retinopathy (DR) is a major cause of vision impairment among diabetics, with significant regional variations in its prevalence and associated risk factors across India. Aims: This study aims to assess the variation in risk factors for DR, including demographic and behavioral characteristics, and to identify regional differences in the severity of DR across four geographic zones in India. Settings and Design: Data were sourced from the INDO EYE registry, encompassing six tertiary eye care hospitals across India. The study was designed to analyze and compare DR-related variables among different geographic zones: south, central, west, and east. Subjects and Methods: The study analyzed data from 7112 eyes of 3699 patients diagnosed with DR. Demographic, clinical, and behavioral data were collected, including age, gender, substance abuse history, comorbidities, and DR severity . Statistical Analysis Used: Descriptive statistics summarized demographic and clinical characteristics. Chi-square tests assessed associations between categorical variables, and one-way ANOVA evaluated continuous variables across zones. Statistical significance was set at P < 0.05, with analysis performed using the IBM SPSS Statistics 28. Results: The study revealed significant regional differences in DR severity and risk factors. The central zone had the highest proportion of proliferative DR and diabetic macular edema, while the south and west zones showed better visual outcomes and higher proportions of certain comorbidities. The east zone exhibited higher substance abuse rates and a broader range of visual acuity outcomes. Conclusions: Regional disparities in DR prevalence and severity highlight the need for targeted public health strategies to address local risk factors and improve diabetes management across India. Enhanced healthcare access and tailored interventions are crucial for reducing DR-related vision loss.